Montenegro : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Montenegro. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2019)
This 2019 Article IV Consultation with Montenegro highlights that while the implementation of large publicly financed infrastructure projects has added economic growth, the accompanying use of fiscal resources has contributed to a large increase in government debt including guarantees, which reached 79 percent of gross domestic product in 2018. Despite the recent intervention in two non-systemic domestic banks, the overall banking sector exhibits improving asset quality, strong credit growth, high liquidity, and is well capitalized. Efforts to improve banking and Anti-Money Laundering/Combating the Financing of Terrorism (AML/CFT) supervision are paramount. The emphasis should be a shift to risk-based tools for supervision in both off-site and on-site functions, and the establishment of a stronger supervisory structure within the central bank. The main priorities are reduction of the labor tax wedge and implementation of the new labor law that aims to increase labor market flexibility. Future decisions on the minimum wage should consider a broad set of indicators and require careful analyses of the impact of past increases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet